A series resistance extraction method for health evaluation of photovoltaic modules - Wang, Shinong; Wu, Hongwei; Ge, Yuan; Liu, Shilin; Ahmed Amer, Ragab (Frontiers in Energy Research, 2024)
Photovoltaic (PV) modules must be monitored and evaluated in real-time during long-term operations to maintain a high performance, and series resistance is a critical component of this process. However, existing series resistance extraction methods may have either low accuracy or a very complex solution process. Worth mentioning, the size of this series resistance depends on environmental conditions, and the extraction results under different environments cannot be mutually referenced and compared. In this study, an analytical method for series resistance was derived, and a correction method for I-V curves that differs from the IEC 60891 standard was proposed, based on the derivative of the I-V characteristic curve of PV modules. The proposed analytical method was compared with three other methods for PV modules with three varied materials, and the influence of the ideality factor on parameter accuracy was also assessed. The obtained results showed that the proposed method can achieve high accuracy through an analytical expression. In addition, the I-V curves of a PV module operating for more than six years were corrected to fit the expected environmental conditions via the proposed correction method. Upon the calculated average value of the series resistance, the results indicated that the PV module has slightly aged, which verifies the effectiveness of the recommended method.